GENETIC BARCODING FOR SURVEILLANCE OF VIRULENCE PLASMIDS IN METAGENOMIC SAMPLES OF MICE GUT MICROFLORA - Shilov , S.V.; Korotetskiy, I.S.; Reva , O.N.; Kuznetsova, T.V.; Zubenko, N.V.; Ivanova , L.N.; Parenova, R.A.; Izmailov, T.Kh. (Eurasian Journal of Applied Biotechnology, 2023)
Outbreaks of nosocomial infections strike the public health system around the world. Current surveillance systems for infectious agents either take too long to identify pathogens or lack the necessary sensitivity to distinguish the virulent strains from the benign ones in the resident microflora. To address this problem, we propose a method for improving the sensitivity and specificity of detection of virulent clonal lines of bacteria or individual virulence plasmids in metagenomic samples. In this study, we used previously developed computational tools, Barcode Generator and Barcoding 2.0, to analyse gut microflora of laboratory mice infected with a pathogenic multidrug-resistant S. aureus and treated with cefazolin, an iodine-containing complex CC-195, and by a combinatorial treatment. We searched the metagenomic samples for representatives of pathogenic microflora using diagnostic genetic barcodes, which were designed based on the whole genome sequences of a collection of clinical isolates. Our results demonstrated a practical applicability of these diagnostic barcodes to monitor clonal lines of pathogens and even individual virulence plasmids in the environment. We also found that the novel drug CC-195 promotes a speedy restoration of the normal gut microflora disturbed by infection and administration of the antibiotic cefazolin.